2018
DOI: 10.3386/w24487
|View full text |Cite
|
Sign up to set email alerts
|

Health and Mental Health Effects of Local Immigration Enforcement

Abstract: We study the effect of two local immigration enforcement policies-Section 287(g) of the Illegal Immigration Reform and Immigrant Responsibility Act and the Secure Communities Program (SC)-that have escalated fear and risk of deportation among the undocumented on the health and mental health outcomes of Latino immigrants living in the United States. We use the restricted-use National Health Interview Survey for 2000-2012 and adopt a difference-indifference research design. Estimates suggest that SC increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 49 publications
3
37
0
Order By: Relevance
“…Yet law enforcement jurisdictions did not begin to participate in immigration enforcement until 2002–03. Participation grew slowly, but by 2009 76 state and local jurisdictions (covering at least one-fifth of all U.S. counties) had 287g agreements with Immigration and Customs Enforcement (ICE) (140). The launch of the Secure Communities (SComm) program in 2008 further amplified the role of law enforcement in immigration enforcement by requiring that local police match fingerprints of all arrested individuals with an ICE database to screen for immigration violations.…”
Section: Pathways Of Influencementioning
confidence: 99%
See 3 more Smart Citations
“…Yet law enforcement jurisdictions did not begin to participate in immigration enforcement until 2002–03. Participation grew slowly, but by 2009 76 state and local jurisdictions (covering at least one-fifth of all U.S. counties) had 287g agreements with Immigration and Customs Enforcement (ICE) (140). The launch of the Secure Communities (SComm) program in 2008 further amplified the role of law enforcement in immigration enforcement by requiring that local police match fingerprints of all arrested individuals with an ICE database to screen for immigration violations.…”
Section: Pathways Of Influencementioning
confidence: 99%
“…One set of quantitative studies attempts to identify the causal effects of policies. These studies often utilize variation in the timing and implementation of policies across states/counties together with variation in the populations affected by policy changes within states/counties (e.g., 63, 86, 102, 140, 146). Essentially, the difference in the effects of policies before and after implementation are compared for the populations affected by the policy change (e.g., noncitizens) versus those not affected (or less affected) by the policy change (e.g., U.S. citizens).…”
Section: Identification and Measurement Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2010 analysis examining the effect of detention and deportation on Latinx families and children in the wake of the Antiterrorism and Effective Death Penalty Act, the IIRIA, and the PATRIOT Act found that higher levels of legal vulnerability corresponded to a greater impact of detention or deportation on several critical aspects of their lives, including parent emotional well-being, ability to provide financially, relationships with children, children’s emotional well-being and academic performance, and ultimately, poor outcomes for children [ 32 ]. A study assessing the health and mental health effects of Section 287(g) of the INA and the Secure Communities Program on mixed-status households identified a causal relationship between local immigration enforcement policies and adverse effects on the health and mental health status of mixed-status Latinx households [ 33 ].…”
Section: Resultsmentioning
confidence: 99%